The Role of Law in the Poverty Reduction Strategy - Lantik Kusuma Aji (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Poverty reduction strategy must be executed properly in order to run development are able to accelerate the implementation of poverty reduction programs. This study aims to analyze the legal role in poverty reduction strategy. This study uses the method of normative legal research done by researching library materials or secondary data alone. Laws are patterns of institutionalized social behavior, exist as a social empirical variables. The data collection is done with the documentary studies and observations in order to obtain primary data and secondary data. Analysis of data using qualitative analysis inductive logic thinking. The results showed that the law plays an important role as a foundation to set poverty reduction strategy. Implementation of legal products is still not entirely on target. The poverty rate still can not be reduced to the maximum. Poverty reduction strategies in the region must be completely in accordance with the level of needs and benchmarks that have been set by the central government. In theory the working of the law can be explained: 1) Component Structure Law, the implementation of poverty reduction has been coordinated. Secretariat of the Vice President established the National Team to Accelerate Poverty (TNP2K). At the level of government district or city, poverty alleviation legal structure led by deputy regent and cooperate with related government agencies are Bappeda and related local government offices including the Department of Education, Department of Health, Department of Public Works, Social Service Manpower and Transmigration, Department of Agriculture Plants food and Horticulture, Department of Cooperatives, SMEs and Industry, and other appropriate agencies of local government respectively. ; 2) Substance Components law, regulation on accelerated poverty reduction strategy already has a foundation of clear laws that have a strong foundation in planning strategies for the right target. But there is no regulation governing the sanction of the central government to local governments that do not run the regional poverty reduction strategy in accordance with the provisions of the central government; 3) the accuracy of regional poverty reduction target acceleration may be constrained by political factors. Regional winner of the election will get the infrastructure development that support economic growth. A poor area and is the target of poverty reduction can be marginalized because of the attitude that is more concerned with the acquisition of sound regional elections. Keywords : development strategy, poverty reduction, the role of law on economy